Metabolic and kinematic responses while walking and running on a motorised and a curved non-motorised treadmill. Issue 4 (16th February 2019) - Bruseghini, Paolo; Tam, Enrico; Monte, Andrea; Capelli, Carlo; Zamparo, Paola
ABSTRACT: The purpose of this study was to assess metabolic and kinematic parameters (contact and flight time, step length and frequency) while walking at the preferred speed (1.44 ± 0.22 m · s −1 ) and while performing an incremental running test (up to exhaustion) on a motorised treadmill (MT) and on a curved non-motorised treadmill (CNMT). Twenty-five volunteers (24.1 ± 3.4 years; 64.7 ± 11.2 kg) participated in the study. Maximal running speed on MT was significantly larger (P < 0.001) than on CNMT (4.31 ± 0.50 vs. 3.75 ± 0.39 m · s −1 ) but no differences in heart rate or oxygen uptake( V ˙ O 2 ) were observed at this speed. The energy cost of walking (Cw ) and running (Cr ) were significantly greater (P < 0.001) on CNMT than on MT (37 and 17%, respectively). No major differences in kinematic parameters were observed at paired, submaximal, running speeds (2.22–3.89 m · s −1 ) butV ˙ O 2 was systematically larger in CNMT (of about 340 ml · min −1 · kg −1 ). This systematic difference can be expressed in terms of a larger "equivalent speed" on CNMT (of about 0.42 m · s −1 ) and should be attributed to factors other than the kinematic ones, such as the belt characteristics (e.g. friction, type of surface and curvature).